From Control to Collaboration: A Philosophical Reinterpretation of Classroom Management through a Positive Discipline Approach in the Context of Elementary Schools - Isnawati, Iis; Hidayat, Ujang Syarif; Winarni, Wiwin (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2025)
This study reviews the paradigm shift in classroom management in elementary schools from a control approach to collaboration through positive discipline. Until now, classroom management practices have been characterized by teacher domination, unilateral rule-setting, and discipline enforcement based on punishment and reward-punishment systems. Findings from a case study at a public elementary school in Sukabumi Regency show that the control approach is still very strong, especially in upper grades, which impacts low student participation, initiative, and self-confidence. However, in lower grades, positive discipline has begun to be implemented, where teachers involve students in rule-making, emphasize dialogue, reflection, and reinforcement of good behavior. This shift reflects a paradigm change from behaviorism to humanism and critical education, which views students as active and equal subjects. The implication of these findings is the need for teachers and schools to adopt collaborative and positive discipline approaches to create a more humanist, democratic, and character-oriented learning environment. Institutional support and ongoing training are key to the successful implementation of this change.